Eastern Sumbanese Bird Classification and Nomenclature: Additions and Revisions - Forth, Gregory (Ethnobiology Letters, 2016)
Expanding on previously published research into folk classification of birds in the eastern part of the Indonesian island of Sumba, this article reports new information on bird categories and classification recorded by the author in 2015. New folk taxa are described and identified and scientific identifications for previously reported taxa are added or revised. Information on local bird classification from the Kambera region is compared with data recorded in the 1970s in the district of Rindi, and these are shown to reveal only minor differences. Employing Berlin’s well-known analytical scheme, the main features of the taxonomy are summarized and totals are enumerated for monotypic and polytypic folk-generics and both named and unnamed (covert) folk-intermediates. Additional information is provided concerning symbolic uses of bird categories, including bird names used as place names and local beliefs about nightjars (Camprimulgus spp.) which correspond to ideas encountered on the ethnozoologically better-known neighboring island of Flores.